Report method and its Application in Memorizing Arabic Vocabulary among Islamic Middle School Students - Intan, Intan; Jamil, Khorul (Tanwir Arabiyyah: Arabic as Foreign Language Journal, 2024)
In language learning especially Arabic, there are many methods used by teachers so that the material presented is easily understood by students one of which is using the takrir method. Nurul Ilmi Integrated Islamic Middle School still has class VII students who have minimal understanding and motivation to learn about Arabic and have difficulty pronouncing Arabic vocabulary and reading, so to overcome this, it is necessary to apply good methods, one of which is the takrir method. This research is qualitative research with a case study type of research from data obtained through interviews, observation and documentation. The purpose of this research is to determine the application of the takrir method in memorizing vocabulary in Nurul Ilmi Integrated Islamic Middle School class VII and to determine the supporting and inhibiting factors. Based on the research results, it shows that learning Arabic vocabulary using the takrir method at the Nurul Ilmi Integrated Islamic Middle School begins with opening activities such as praying, greeting the teacher and students. After that, in the core activity of the takrir method in memorizing Arabic vocabulary, the teacher will first guide the students to read the vocabulary that will be memorized, then the theacher will mention vocabulary from Indonesian up to three times and students will answer the vocabulary using Arabic up to three times. And ended with assignments and questions and answers. The supporting factor for implementing this assessment method is that it makes it easier for students to memorize vocabulary, while the inhibiting factor is the student’s mood and condition.